Investigation of MIS capacitor with TiO2 thin film as insulator prepared by low temperature arc vapor deposition (LTAVD) process - Shubham K.; Khan R.U.; Chakrabarti P. (My University, 2025)
A technological approach for Low temperature arc vapor deposition (LTAVD) processing of stabilized thin film Titanium Dioxide (TiO2) on n-type Si (100) substrate has been extensively investigated in this paper. The surface and structural morphology of TiO2 thin film has been studied by Scanning Electron Microscopy equipped with Energy Disperse X-ray Spectrometer (SEM-EDX) and X-ray diffraction (XRD). Some TiO2 crystal randomly distributed on Si substrate but TiO2 thin film shows high quality amorphous nature. The capacitance-voltage and current-voltage characterizations were studied at room temperature (300 K) for Pd/TiO2/n-Si based MIS structure. Further capacitance-voltage fabrication result has also been compared with numerical simulation data obtained at signal frequency 1MHz using the commercially available ATLASTM, a two dimensional device simulator from SILVACO. © 2012 IEEE.